Application of 3D digital technologies in paleontological reconstruction: a systematic literature review - Zheng, Lu; Che Me, Rosalam; Rahmat, Rahmita Wirza O.K. (Cogent OA, 2025)
Paleontology, the study of ancient life through fossilized remains, has experienced a transformative shift with the advent of digital technologies. Traditional methods such as manual reconstruction, molding, and casting, though foundational, are often time-consuming and risk damaging valuable specimens. In response, the field has embraced “virtual paleontology,” which employs three-dimensional (3D) digital tools to reconstruct, visualize, and study fossils. This study presents a systematic literature review on the application of three-dimensional digital technologies in paleontological reconstruction. The methodology consists of four steps: formulating the research problem, conducting a literature search, selecting studies, and extracting the data. Initially, 1275 peer-reviewed articles were gathered from five databases (ScienceDirect, Scopus, Web of Science, Google Scholar, IEEE), and 48 articles published between 2013 and 2024 were selected. These articles specifically address the use of three-dimensional digital technologies in paleontological reconstruction and research, and despite promising developments, this review acknowledges the challenges and limitations associated with digital restoration. Technical challenges, including data acquisition and software complexity, are discussed. Looking toward the future, the review outlines potential advancements and innovations in digital reconstruction. The importance of collaborative efforts and interdisciplinary approaches has been emphasized as the field pushes the boundaries of digital restoration capabilities.